Progress on Transition Metal Ions Dissolution Suppression Strategies in Prussian Blue Analogs for Aqueous Sodium-/Potassium-Ion Batteries - Shu, Wenli; Li, Junxian; Zhang, Guangwan; Meng, Jiashen; Wang, Xuanpeng; Mai, Liqiang (Nano-Micro Letters, 2024)
Aqueous sodium-ion batteries (ASIBs) and aqueous potassium-ion batteries (APIBs) present significant potential for large-scale energy storage due to their cost-effectiveness, safety, and environmental compatibility. Nonetheless, the intricate energy storage mechanisms in aqueous electrolytes place stringent requirements on the host materials. Prussian blue analogs (PBAs), with their open three-dimensional framework and facile synthesis, stand out as leading candidates for aqueous energy storage. However, PBAs possess a swift capacity fade and limited cycle longevity, for their structural integrity is compromised by the pronounced dissolution of transition metal (TM) ions in the aqueous milieu. This manuscript provides an exhaustive review of the recent advancements concerning PBAs in ASIBs and APIBs. The dissolution mechanisms of TM ions in PBAs, informed by their structural attributes and redox processes, are thoroughly examined. Moreover, this study delves into innovative design tactics to alleviate the dissolution issue of TM ions. In conclusion, the paper consolidates various strategies for suppressing the dissolution of TM ions in PBAs and posits avenues for prospective exploration of high-safety aqueous sodium-/potassium-ion batteries. Highlights: 1 Comprehensive insights into Prussian blue analogs for aqueous sodium- and potassium-ion batteries. 2 Unveiling the dissolution mechanism of transition metal ions in Prussian blue analogs. 3 Innovative solutions to suppression transition metal ion dissolution, spanning electrolyte engineering, transition metal doping/substitution, minimize defects, and composite materials.